2018
DOI: 10.2105/ajph.2018.304321
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed HIV and HCV Infection in a New York City Emergency Department, 2015

Abstract: Undiagnosed HCV was more prevalent than undiagnosed HIV in this population, suggesting that aggressive testing initiatives similar to those directed toward HIV should be mounted to improve HCV diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…ICER values calculated from birth cohort and general population screening compared to no screening with ED seroprevalence varied over a broad range of estimates. Reference lines represent varying seroprevalence measures obtained from observational studies of HCV measured in different EDs 8‐10,21‐24. Shaded regions represent the 95% confidence intervals around each line of best fit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ICER values calculated from birth cohort and general population screening compared to no screening with ED seroprevalence varied over a broad range of estimates. Reference lines represent varying seroprevalence measures obtained from observational studies of HCV measured in different EDs 8‐10,21‐24. Shaded regions represent the 95% confidence intervals around each line of best fit.…”
Section: Resultsmentioning
confidence: 99%
“…Locally weighted smoothing was used to create trend lines through a scatterplot with their respective 95% confidence interval bands to observe the relationship between seroprevalence measures and the resulting incremental cost‐effectiveness ratios (ICERs) per screening strategy when compared to no screening. Seroprevalence measures from published observational studies across multiple EDs were used as reference values to demonstrate the potential cost‐effectiveness of a similar screening programme offered in different ED settings 8‐10,21‐24 Ranging Linkage to Care: Because the benefits of screening are lost without linkage to further care and treatment, univariate sensitivity analysis was performed varying the probability of linkage to care parameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study found an HCV seroprevalence of 3.9% among patients visiting a New York City emergency department (ED), and 19.2% of those cases were previously undiagnosed. Among undiagnosed HCV cases in that study, 39.5% of cases would be missed through birth cohort screening . Gaps in screening may also exist in primary care specialties that mainly care for patients outside the birth cohort.…”
Section: Introductionmentioning
confidence: 86%
“…Many health organizations have made HCV elimination a priority, but too often the “test and treat” paradigm gets stalled after the first step. In a study from a New York City Emergency Department, 80% of the people testing positive for HCV RNA (the definitive biomarker of infection) already had a positive HCV RNA test in their medical record (Torian et al, 2018). Importantly, ∼70% of the HCV RNA–positive patients were born between 1945 and 1965 and thus are part of the baby boomer cohort (Torian et al, 2018).…”
Section: Hepatitis C Virus (Hcv): Test Treat and Find A Way To Manage The Damage Left Behindmentioning
confidence: 99%